IMPARTING PEACE EDUCATION THROUGH COSCHOLASTIC ACTIVITIES AT THE SCHOOL LEVEL - Das, Swarnalata; Das, Kalpana Kalita (European Scientific Journal, ESJ, 2014)
Despite tremendous advances in science and technology in the twentieth century the present world is witnessing violence, wars terrorism and conflicts to a large extent. In the modern civilized world today, the material development has crossed all the boundaries but at the same time human miseries and pain has been as such that has been never before in the history of mankind. There is no doubt that the techno scientific development today has helped mankind to reach the apex of material development but at the same time human society has also become a victim of war, terrorism, weapons of mass destruction, population menace, environmental destruction, poverty, hunger, illiteracy, over politicization of civil society, globalization, moral decay of human being and consequent psycho physical diseases. Today, the world is shrinking to a global village on one hand and on the other hand there is a growing intolerance amongst the people. Violence of all form has become very common in all the societies of the world. There is a negative trend prevailing in the societies all over the world. Under such considerations peace education has become a necessity of the present time. Co- scholastic activities in the school should be used as a vehicle for imparting Peace Education to the students. At school the children shows great enthusiasm to participate in different co- scholastic activities. The school should take this opportunity and adopt some specific ways to inculcate peace in the minds of the students through different co- scholastic activities. This paper has undertaken two objectives: 1. To study the need of co-scholastic activities for imparting peace education in the school. 2. To study the role of co-scholastic activities in imparting peace education to the students.